THE EXISTENCE OF BAHASA INDONESIA IN UNIVERSITIES FOR THE DEVELOPMENT OF STUDENT CHARACTER - Gusnia Gusnia; Yunisa Oktavia (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
In the context of speaking good Indonesian, it is very important to have the role of an educator in building this great nation, especially in terms of language speech, which we know for ourselves that Indonesia is famous for its hospitality, and of course it becomes a proof that educators play an important role. great. Globalization plays a superior role in the realm of the world of education, not only entering the world of technology but also entering the realm of morality of a nation, for example, in the use of Indonesian, we frequently hear the intermingling of cultures that almost makes the existence of the use of Indonesian. It falls short of making Indonesian a unifying language by implementing the youth oath.